A Different Certification Effect of the Small Business Innovation Research (SBIR) Program: Evidence From the Kauffman Firm Survey. (November 2016) - Galope, Reynold V.
This study examines the role of public investments in inducing small firms to develop risky, early-stage technologies. It contributes to expanding our understanding of the consequences of high-technology policies by investigating in more depth the effect of the Small Business Innovation Research (SBIR) program on the innovation effort and ability to attract external capital of small business start-ups using a new sample and estimation approach. The authors found empirical evidence that the public cofinancing of private research and development has a positive effect on the innovation propensity of small high-tech start-ups. However, contrary to theoretical expectations, they did not find any significant "certification effect" of receiving an SBIR award on attracting follow-on investment. What the authors discovered is a different certification effect: SBIR recipient firms are more likely to attract external patents. This finding confirms that enterprises need to orchestrate a portfolio of internal and external knowledge assets to produce innovations with unique competitive advantage.